Web-Based Electrical Customer Service System - Frebian, Muhammad Rizki; Riyadi, Slamet; Purbohadi, Dwijoko (Universitas Muhammadiyah Yogyakarta, 2022)
The Electricity Customer Service Information System is a website for making new electricity requests and changing electrical power. Along with the development and advancement of technology, industrial technology is closely related to electric power, one of the most significant aspects that vigorously supports the development, particularly in the Information Technology sector in the urban world. Electric power is a fundamental element for enhancing the welfare of society. Therefore, electrical energy is a measure of societal development. Thus, a website-based information system was developed employing an observational data-gathering technique. This study utilized System Development Live Cycle (SDLC) as the system development approach, Unified Modeling Language (UML) for system analysis and design, PHP as the programming language, and MYSQL as the database.